Metafictional potentiality of detective fiction and the metaphysical detective stories - Izdebska, Agnieszka (Zagadnienia Rodzajów Literackich, 2020)
The article examines metatextual devices appearing within texts whose genre affiliation — the implementation of the detective novel convention — is unarguable. Such use of selfreferential strategies is juxtaposed with their applications in texts that in English-language reflection on postmodern and modernist novels are defined as metaphysical detective stories. The article examines the genre aspects of the use of these devices and their consequences for the location of a crime novel within contemporary popular culture.